Telefonsko svetovanje kot element integrirane zdravstvene nege in oskrbe bolnikov z demenco in svojcev - Mikluž, Branka (Obzornik zdravstvene nege, 2005)
The artcle presents the use of a telephone counselling line in comprehensive treatment of patients with dementia and their family members. The aim of the research study was to establish the quality of services through the experienceof help seekers. ln the first part the organisational baselines of atelephone counselling line are descrihed. There is also a short review of organised activities focused on helping patients with dementia and their family members, both abroad and in Slovenia, and their experience with this kind of work. This is followed by the analysis of the results of the research on the quality of services provided by the telephone counselling line Forget me Not. The evaluation of the quality was assesed by the following indicators:users satisfaction, the way of help, adequacy of aceessibility of the telephone counselling line and searching for that kind of help in the future. The resalts showed that most users received the information they were looking for and show that telephone counselling indeed helps people when they found themselves in distress. The author concludes that this kind of work is an important element of integrated nursing care, for patients with dementia, and that it contributes to the guality of life of patients as well as their family members.
Keywords: ankete; Demenca; Dementia; Health Education; Nursing; Questionnaires; svetovanje; Telefon; telefonsko svetovanje; Telephone; zdravstvena nega; Zdravstvena vzgoja